ChemInform Abstract: Syntheses, Characterization and Magnetic Properties of Two Novel Inorganic—Organic Tungstoferrites, [Fe4III(H2O)2 (B‐α‐FeIIIW9O34)2] 10‐. Issue 16 (28th March 2013) - Zhang, Dongdi; Wang, Chunzhang; Li, Suzhi; Liu, Jiangping; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract The new compounds (III) and (IV) crystallize in the triclinic space group P <![CDATA[$\bar 1$]]> <inline-graphic xlink:href="ark:/27927/pgg1x53zxj9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with Z = 2 (single crystal XRD).